Template GNL-assisted synthesis of porous Li1.2Mn0.534Ni0.133Co0.133O2: towards high performance cathodes for lithium ion batteries. Issue 32 (10th April 2015) - Huang, Yanling; Hou, Xianhua; Ma, Shaomeng; Zou, Xiaoli; Wu, Yuping; Hu, Shejun; Shao, Zongping; Liu, Xiang
<x xml:space="preserve">Abstract</x> A high performance cathode of porous Li1.2Mn0.534Ni0.133Co0.133O2 for lithium ion batteries synthesized by a GNL-template.